A Novelist in Changing Rooms: Motherhood and Auto/Biography - Nicolas Pierre BOILEAU (E-REA, 2013)
A Life’s Work, Cusk’s first memoir, in which she recounts her experience of motherhood, remains Cusk’s most controversial work. She tries to grasp the feeling of estrangement she experienced when she gave birth and the way bonding with her daughters was a slow process rather than an instantaneous event. What critics have tended to focus on is what I would call the thematic reading of this text – the sociological and cultural debate that it opens up about the representation of what motherhood is –, these discourses which Cusk attacks. However, they have failed to address the literary implication of Cusk’s appropriation of memoir writing, which, because it is defined by something which is impossible – at attempt at capturing the reality of an experience which is idealised, imaged and partly beyond words – gives way to creative solutions that undermine preconceived ideas about both the feelings motherhood should engender and the form any account of that experience should take. Written from a Lacanian perspective, this article addresses the scandalous nature of a creative memoir on motherhood.